2017
DOI: 10.1002/pits.22022
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Synthesis of the Effect of Standard Error of Measurement on Decisions Made Within Brief Experimental Analyses of Reading Fluency

Abstract: Intervention researchers often use curriculum-based measurement of reading fluency (CBM-R) with a brief experimental analysis (BEA) to identify an effective intervention for individual students. The current study synthesized data from 22 studies that used CBM-R data within a BEA by computing the standard error of measure (SEM) for the median data point from the baseline and intervention data. The median CBM-R score from the intervention that the authors of each study identified as most effective fell within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Mean difference data have strengths and limitations for interpreting ATD data, but according to Manalov and Onghena (2017), they are the most common form of quantification in ATDs and can be particularly useful when data patterns (even nonlinear patterns) are similar across conditions. By calculating means across conditions, this also allowed for a relatively straightforward method of examining whether mean differences between conditions exceeded what might be expected simply from measurement error, which is increasingly being used in single-case experimental design (SCD) research (e.g., Burns et al, 2017;Ross & Begeny, 2015). Although there are no known standard error of measurement (SEM) data available for the specific ORF passages used in this study, tertiary analysis of mean differences relied upon known estimates of SEM for third-grade ORF passages.…”
Section: Oral Readingmentioning
confidence: 99%
“…Mean difference data have strengths and limitations for interpreting ATD data, but according to Manalov and Onghena (2017), they are the most common form of quantification in ATDs and can be particularly useful when data patterns (even nonlinear patterns) are similar across conditions. By calculating means across conditions, this also allowed for a relatively straightforward method of examining whether mean differences between conditions exceeded what might be expected simply from measurement error, which is increasingly being used in single-case experimental design (SCD) research (e.g., Burns et al, 2017;Ross & Begeny, 2015). Although there are no known standard error of measurement (SEM) data available for the specific ORF passages used in this study, tertiary analysis of mean differences relied upon known estimates of SEM for third-grade ORF passages.…”
Section: Oral Readingmentioning
confidence: 99%
“…ORF measure is considered as the most critical measurement in R-CBM since 1982 (Deno, Mirkin, & Chiang) and therefore the existing literature on ORF, over the last 10 years, focuses particularly on issues such as its utility for reading difficulties identification in other languages (Protopappas & Skalumbakas, 2008), probe equivalence (Christ & Ardoin, 2009), the way of graphically representing progress (Christ, Silberglitt, Yeo, & Cormier, 2010), whether R-CBM measurements can be used as indicators on the impact of teaching methods used by teachers (Petscher, Cummings, Biancarosa, & Fien, 2013), how to use the data resulting from monitoring the progress for the educational decision-making process (Burns et al, 2017;Van Norman & Christ, 2016) and the degree of correlation with reading comprehension (Shin & McMaster, 2019).…”
Section: Curriculum Based Measurement In Readingmentioning
confidence: 99%
“…However, comparing so few data points—minimally two—may be insufficient in reducing decision-making errors to a level that justifies use of BEA (Andersen et al, 2013; Mercer, Harpole, Mitchell, McLemore, & Hardy, 2012). That is, BEA does not account for the uncertainty of conclusions based on the sampling distribution of the outcome (Burns et al, 2017). Importantly, this perspective on BEA assumes a true population parameter exists and error is produced from factors orthogonal to the variability produced by the independent variable (i.e., classical test theory; CTT).…”
Section: Effect Of Probe Variabilitymentioning
confidence: 99%
“…Relatedly, Burns et al (2017) used existing reports to approximate the SEM of the probes used in published BEAs that focused on reading. The authors reported that approximately 25% of reviewed studies had overlapping 68% confidence intervals, highlighting the errors that may occur during BEA.…”
Section: Effect Of Probe Variabilitymentioning
confidence: 99%
See 1 more Smart Citation